The determinants of public sector size: Theoretical approaches and empirical estimates for local government in the Federal Republic of Germany - Adrian Bothe (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1986)
The growth of government has become a global phenomenon which, over the years, has attracted a great deal of attention and continues to do so. This growth has not been uniform, neither in time nor in space, and it was the factors underlying these differences interest has focused on. No comprehensive theory, however, has yet emerged from the prolific and varied literature. Instead, a number of approaches was developed, each of them an incomplete explanation of a complex phenomenon. A problem common to all of them when it comes to testing hypotheses empirically, is the measurement of total public sector economic activity. For lack of data, it is usually approximated by public expenditures. Most probably, this understates the role of government in economic life, since many of its activities, while unrecorded in the budget, redirect resources just as taxation and public spending do. Typical examples are consumer and worker safety regulation, public utility price and output regulation in certain industries, and tax expenditures.
Keywords: 330; Öffentlicher Sektor; Öffentliche Ausgaben